2021
DOI: 10.1002/vms3.511
|View full text |Cite
|
Sign up to set email alerts
|

Extract of neem (Azadirachta indica) leaf exhibits bactericidal effect against multidrug resistant pathogenic bacteria of poultry

Abstract: The aim of the study was to determine the efficacy of neem leaf extract against multidrug resistant (MDR) pathogenic bacteria. Laboratory stock culture of Pasteurella multocida, Salmonella pullorum, Salmonella gallinarum and Escherichia coli was revived. Antibiogram profiles of these bacteria were determined by disc diffusion method. Ethanolic extract of neem leaf was prepared. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of neem leaf extract (112.5, 100, 50, 25, 12.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A study done by Altayb et al [ 23 ] demonstrated that the methanolic extract of A. indica contains various bioactive compounds, such as beta-D-mannopyranoside and O-geranyl, which are capable of inhibiting the growth of various bacterial strains. Raghavendra et al [ 24 ] studied the antifungal and antimicrobial activity of the neem, and the findings demonstrated superior results when compared with 3% sodium hypochlorite (NaOCl). The acetone extracts of neem were more effective at inhibiting bacterial growth compared to aqueous extracts, which indicates the influence of solvents against bacteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Altayb et al [ 23 ] demonstrated that the methanolic extract of A. indica contains various bioactive compounds, such as beta-D-mannopyranoside and O-geranyl, which are capable of inhibiting the growth of various bacterial strains. Raghavendra et al [ 24 ] studied the antifungal and antimicrobial activity of the neem, and the findings demonstrated superior results when compared with 3% sodium hypochlorite (NaOCl). The acetone extracts of neem were more effective at inhibiting bacterial growth compared to aqueous extracts, which indicates the influence of solvents against bacteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also possess the characteristics of anti-inammation, antibacterial, antifungal, antimalarial, antidiabetic, and antiviral. 20,21 Literature study revealed the presence of multiple phytochemicals in the leaves extract of the neem plant. The most common of these components are alkaloids, avonoids, tannins, steroids, and saponins.…”
Section: Phytochemicals In Azadirachta Indicamentioning
confidence: 99%
“…Alkaloids, terpenoids, saponins, flavonoids, phenols, tannins, steroids, and aldehydes Ali et al, 2021 [103] Bangladesh…”
Section: Leaves Extractmentioning
confidence: 99%